(untitled) (PANGEEA, 2025)
The challenges that the elderly face in their everyday life are inexhaustible and at the same time complex, requiring the development and implementation of measures, public policies of social support for this segment of the population in which all perspectives of aging are included. The social perceptions of the elderly, as well as the debates circulated regarding the s̈ocial costïnvolved in the support aimed at them, represent broad topics of discussion in the design of social services dedicated to them. In the implementation of social policies, several well-defined directions of action were included, such as: social integration of the elderly; aging and addiction prevention policies; recovery, reactivation and social insertion programs; home maintenance; organizing support networks and alternative care, etc.